2017
DOI: 10.1016/j.ebiom.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of PTP1B Attenuates Hypothalamic Inflammation via Activation of the JAK2-STAT3 Pathway in Microglia

Abstract: Protein tyrosine phosphatase 1B (PTP1B) regulates leptin signaling in hypothalamic neurons via the JAK2-STAT3 pathway. PTP1B has also been implicated in the regulation of inflammation in the periphery. However, the role of PTP1B in hypothalamic inflammation, which is induced by a high-fat diet (HFD), remains to be elucidated. Here, we showed that STAT3 phosphorylation (p-STAT3) was increased in microglia in the hypothalamic arcuate nucleus of PTP1B knock-out mice (KO) on a HFD, accompanied by decreased Tnf and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 53 publications
1
36
1
Order By: Relevance
“…STATs are highly associated with the expression of proinflammatory cytokines [33]. In this study, we found that DSS exposure markedly reduced mRNA abundance of STAT3 in Caco-2 and HT-29 cells compared with the control group (P<0.05) (Fig.…”
Section: Mir-135a Mimic Activated Stat Signal In Caco-2 and Ht-29 Cellsmentioning
confidence: 50%
“…STATs are highly associated with the expression of proinflammatory cytokines [33]. In this study, we found that DSS exposure markedly reduced mRNA abundance of STAT3 in Caco-2 and HT-29 cells compared with the control group (P<0.05) (Fig.…”
Section: Mir-135a Mimic Activated Stat Signal In Caco-2 and Ht-29 Cellsmentioning
confidence: 50%
“…It has been also shown that PTP1B contributes to hypothalamic inflammation and leptin resistance in rodents fed a HFD . As a matter of fact, PTP1B −/− mice exhibit decreased TNF‐alpha expression, accompanied by increased interleukin‐10 mRNA levels in the hypothalamus, even under HFD‐feeding . Notably, TNF‐alpha has been shown to increase PTP1B expression in hypothalamic organotypic cultures in a dose and time‐dependent fashion .…”
Section: Discussionmentioning
confidence: 97%
“…41 As a matter of fact, PTP1B −/− mice exhibit decreased TNF-alpha expression, accompanied by increased interleukin-10 mRNA levels in the hypothalamus, even under HFD-feeding. 42 Notably, TNF-alpha has been shown to increase PTP1B expression in hypothalamic organotypic cultures in a dose and time-dependent fashion. 43 Nevertheless, despite PTP1B has been consistently shown to mediate insulin and leptin resistance in response to proinflammatory signals including endoplasmic reticulum stress, aging and TNF-alpha, there is still scant evidence regarding the benefit of using PTP1B and TNF-alpha-specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and the hyperleptinemia in obesity are known to drive reactive gliosis, endoplasmic reticulum (ER) stress and the expression of negative regulators of insulin signalling, such as SOCS3, PTP1B and TCPTP within the hypothalamus (Figure b3). The hyperleptinaemia seen in obesity is considered to increase the hypothalamic expression of TCPTP, PTP1B and SOCS3, whereas ER stress and the obesity‐associated inflammation drives the expression of PTP1B and SOCS3 . These negative regulators may be instrumental in the initiation/exacerbation and/or maintenance of cellular leptin and insulin resistance (Figure b3) .…”
Section: Insulin Resistance and Metabolic Diseasementioning
confidence: 99%
“…The hyperleptinaemia seen in obesity is considered to increase the hypothalamic expression of TCPTP, PTP1B and SOCS3, whereas ER stress and the obesity-associated inflammation drives the expression of PTP1B and SOCS3. 91,92,[202][203][204][205][206] These negative regulators may be instrumental in the initiation/exacerbation and/or maintenance of cellular leptin and insulin resistance (Figure 2b3). 59,91,207 In the case of SOCS3, increased expression is seen as early as 2 days in AgRP neurones and 2 weeks in POMC neurones.…”
Section: Insulin Resistance and Metabolic Diseasementioning
confidence: 99%